Process parameter optimization for biodiesel production from mixed feedstock using empirical model. (August 2018) - Antony Miraculas, G.; Bose, N.; Edwin Raj, R.
Highlights: Discarded, underutilized, non-edible mixed feedstock oil is used to extract biodiesel. Two stage esterification processes is used to reduce its FFA content. A multi-variant design of experiments is used to optimize the process parameters for biodiesel extraction. Optimum empirical model is validated by doing experiments. Extracted biodiesel properties are tested using standard test procedure. Abstract: Different feedstocks are available at various quantities in different regions, which are to be exploited to meet the growing demand for biodiesel production. In the present study, raw oil from three non-edible feedstock like Calophyllum Inophyllum, Jatropha curcas and Pongamia Pinnata are mixed in equal proportion and the biodiesel process parameters optimized. Since the acid value of the mixed feed stock is high, two stage esterification-transesterification processes is applied to produce biodiesel. Multi variant empirical model is employed to optimize the influencing process parameters and it is found that methanol concentration is the most significant process parameter followed by the catalyst concentration. Around 98% biodiesel yield is obtained at the optimized condition. The optimized process conditions for the transesterification process are oil/methanol ratio (2.5v/v), catalyst concentration (1.17%w/v), duration (95 min) and temperature (53 °C). The optimum process parameters are validated by experiments and the biodiesel properties tested for its compliance with ASTM standard in order to use it in the existing diesel engine.